Analisis Efektivitas Jalur Ekspektasi Inflasi dan Jalur Suku Bunga Dalam Mekanisme Transmisi Kebijakan Moneter di Indonesia - Kurniasari, Ike Oktaviana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to understand the comparison the expectation of inflation and the interest rates channel in a transmission mechanism of monetary policy in Indonesia. Research approach that is used is descriptive of a quantitative approach .The data used is secondary data sourced from the central bureau of statistics and bank indonesia .Was used in the research methodology time series and granger causality approach and var or vecm .While an instrument the analysis used is 6.0 e-views .This research the period from January 2005 until December 2013. The both channel is equally effective in achieving the final objective of monetary policy. It is just that the level of effectiveness owned each are not alike. Based on results of impulse function , response variance decomposition and time lag, the expectation of inflation is more effective when compared interest rates channel. Â Keywords: The Effectiveness of Monetary Policy, Interest Rate Channel, Expectation Of Inflation Channel, VECM